2019
DOI: 10.5039/agraria.v14i3a5664
|View full text |Cite
|
Sign up to set email alerts
|

Yield in tomato under two water depths and plastic mulching

Abstract: The search for sustainable agriculture is a reality that aims saving water and agricultural inputs to obtain greater productivity. Some techniques can be used for this purpose, such as drip irrigation and the plastic mulch of the soil. Thus, the aim of this study was to verify the effects of plastic mulch under two water depths on the productive characteristics of a commercial tomato field. The employed experimental design was the completely randomized in a 2 x 2 factorial. The sources of variation were two ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(27 reference statements)
2
2
0
Order By: Relevance
“…The positive effect of side coating on the fruit number per plant (Figure 4) is consistent with previous results (Silva et al 2019) that indicated a 12.9% increase in tomato cv. Italian production by the maintenance of soil moisture and the reduction of water losses via irrigation and nutrients.…”
Section: Discussionsupporting
confidence: 92%
“…The positive effect of side coating on the fruit number per plant (Figure 4) is consistent with previous results (Silva et al 2019) that indicated a 12.9% increase in tomato cv. Italian production by the maintenance of soil moisture and the reduction of water losses via irrigation and nutrients.…”
Section: Discussionsupporting
confidence: 92%
“…Regardless of the cover crop used, plastic mulch was the best cover for improving tomato fruit yield and quality. As observed in this study, an increase in commercial yield owing to plastic mulching has also been reported in other studies [34,35]. The most frequently used plastic mulch for vegetable growth is a black polyethylene film, which has very good properties and a relatively low price.…”
Section: Yieldsupporting
confidence: 87%
“…In productive agro-management techniques, water is one of the governing limiting factors among various known factors. Furthermore, it represents a captain's role in active plant growth and productivity (Iqbal et al 2019;Silva et al 2019). It is the most desirable candidate to determine the essence of agriculture (Hanjra and Qureshi 2010).…”
Section: Introductionmentioning
confidence: 99%